Two-dimensional shear rate field and flow structures of a pseudoplastic fluid in a stirred tank using particle image velocimetry. (2nd February 2022) - Ayala, Jenniffer Solange; de Moura, Helder Lima; Amaral, Rodrigo de Lima; Oliveira Júnior, Francisco de Assis; Nunhez, José Roberto; de Castilho, Guilherme José
Graphical abstract: Highlights: Study of a pseudoplastic fluid flow in a stirred tank. Ensemble-averaged and angle-resolved PIV measurements. Experimental data of shear rate, apparent viscosity and Reynolds number fields. Discussion of the effect of the spatial resolution and anisotropy. Estimation of the Metzner-Otto constant using 2D PIV data. Abstract: For non-Newtonian fluids, an accurate determination of the shear rate is essential to optimize process parameters, which can lead to the improvement of the process efficiency. This work proposes the evaluation of an aqueous solution of carboxymethylcellulose (CMC) analyzing two azimuthal planes, AZ 0° and 45°, and four blade positions, AR 0°, 22.5°, 45° and 67.5°, by ensemble-averaged and angle-resolved PIV measurements, respectively, in a stirred tank equipped with a pitched-turbine impeller. Results are shown in terms of time-averaged velocity, shear rate, apparent viscosity and Reynolds number fields. Differences between both PIV measurements approaches were significant in terms of velocity magnitude and characteristics of trailing vortices. The results demonstrate that the shear rate is strongly influenced by spatial resolution. The highest shear rates were obtained in the impeller region. The presence of a vortex above the blade resulted in high values of local Reynolds number, reflecting the presence of turbulence in that region.